FATORES CONTRIBUINTES PARA OCORRÊNCIA DE QUEDAS EM PACIENTES HOSPITALIZADOS SOB A ÓTICA DA SEGURANÇA DO PACIENTE. - COUTINHO, Alan Cássio Carvalho (2019)
Introduction: Fall is the event in which the person inadvertently falls to the ground or lower levels, without intentional change of position. When it happens in a hospital environment, it is the third most frequent adverse event, which can cause physical and emotional discomfort to the patient and increase the costs of treatment. This study is justified by the importance of determining which are the contributing factors for the occurrence of falls, which allows early identification of the circumstances or actions that influence or could influence the event of this event. Objective: To evaluate the occurrence of falls in hospitalized patients in a tertiary hospital in. Method: This is an observational, retrospective study with a quantitative approach, developed in a private tertiary hospital in São Luís, Maranhão, with patients admitted to the clinical, surgical, oncology, pediatric and Intensive Care Unit. Data were collected from the hospital's database for socio-demographic, clinical and event data, Morse Scale and to determine the factors associated with fall, the London Protocol was used. Results: Patients who suffered falls were predominantly males, elderly, married, assessed as high risk for the event, hospitalized in the medical clinic (57.4%), hypertensive patients (39.7%), diabetics (25.0%), with medications of continuous use (55.6%) and some of these drugs increased the risk of falls (32.4%). Regarding the characteristics of the falls, a predominance of those occurring during the morning shift (56.6%), in the room (51.5%) and in the bathroom (46.3%, p <0.001), of height ( 63.2%, p <0.001), in the presence of companions (65.4%), the majority of whom were family members (98.9%) and 68.4% did not present any harm to the patient. The locality of being in the bathroom and falling of the proper height showed statistically significant for the event of the event. Regarding the assessment of the risk of falls, it was performed in 99.3% of the patients, mostly classified as high risk (43.7%), 0.7% of the patients had no risk of falls assessed in their admission of the unit; the use of a risk identification bracelet was present in 95.5% of those evaluated. Conclusion: The contributing factors for the fall were those related to the patient, such as their health condition, known risks and personal issues.